1992
DOI: 10.1073/pnas.89.11.5001
|View full text |Cite
|
Sign up to set email alerts
|

CD43 interferes with T-lymphocyte adhesion.

Abstract: CD43 is a cell-surface sialoglycoprotein of uncertain physiologic function expressed to various degrees by most leukocytes. We tested whether or not CD43 participates in intercellular adhesion by comparing the binding of human T lymphocytes to transfected HeLa cells stably expressing CD43 and sham-transfected HeLa cells (CD43-negative). Significantly fewer T lymphocytes adhered to the CD43-positive HeLa cells than to the CD43-negative HeLa cells. Diminished T-cell adherence to the CD43-positive HeLa cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(106 citation statements)
references
References 32 publications
5
99
2
Order By: Relevance
“…However, our results showing the lack of well developed spleen follicles, defective germinal centres and the presence of T cell-dependent areas depleted of T lymphocytes suggest the absence of the optimal lymphoid architecture required to achieve adequate antigen presentation and costimulation. In this context, our results on the expression of CD43 might be of special relevance given the adhesive features of CD43 [22][23][24]. We found fewer CD43-expressing T cells in the peripheral blood of WAS patients (where more activated/memory T lymphocytes were found) than in controls, and more CD43-expressing T lymphocytes in the spleen of WAS (where naive cells were accumulated) than in the normal individual.…”
Section: Discussionmentioning
confidence: 57%
“…However, our results showing the lack of well developed spleen follicles, defective germinal centres and the presence of T cell-dependent areas depleted of T lymphocytes suggest the absence of the optimal lymphoid architecture required to achieve adequate antigen presentation and costimulation. In this context, our results on the expression of CD43 might be of special relevance given the adhesive features of CD43 [22][23][24]. We found fewer CD43-expressing T cells in the peripheral blood of WAS patients (where more activated/memory T lymphocytes were found) than in controls, and more CD43-expressing T lymphocytes in the spleen of WAS (where naive cells were accumulated) than in the normal individual.…”
Section: Discussionmentioning
confidence: 57%
“…CD43 is important for the function of the immune system and appears to be involved in cell adhesion and cell proliferation. Owing to the structural characteristics of the extracellular domain of CD43, this molecule has both adhesive and antiadhesive properties (Ardman et al, 1992;Ostberg et al, 1996). Although there are no ligands known for the extracellular domain of CD43, ligation of CD43 causes cell signaling probably via the cytoplasmic tail of CD43.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PC, we demonstrated that charge repulsion is the main mechanism involved, because removal of sialic acid from cells overexpressing PC restores normal adhesion properties. The neuronal cell adhesion molecule N-CAM has also been shown to reduce cell-cell and cell-matrix adhesion by charge repulsion when the molecule is polysialylated (Ardman et al, 1992;Yang et al, 1992;Rutishauser and Landmesser, 1996).…”
Section: Discussionmentioning
confidence: 99%